The factors of this equation are x = sqrt(6), x = -sqrt(6) and x = -5.
In order to find these by grouping, we start by just taking the first two terms. We then pull out the greatest common factor.
x^2 + 5x^2
x^2(x + 5)
Now we do the same for the last two.
-6x - 30
-6(x + 5)
Since the two parenthesis left behind are exactly the same, we can use them along with the factors pulled out, multiplied together.
(x^2 - 6)(x + 5)
Now to find the factors, we simply set both parenthesis separately equal to 0.
x + 5 = 0
x = -5
x^2 - 6 = 0
x^2 = 6
x = +/-sqrt(6)